Bachelor of Engineering (Hons.) Electrical (EE220) POs performance analysis based on OBE-ANAS measurement tools / Mohaiyedin Idris - Idris, Mohaiyedin; Zulhanip, Aida Zulia; Hamzah, Irni Hamiza; Ibrahim, Mohammad Nizam; Shafie, Mohd Affandi (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Nowadays, Outcome Based Education (OBE) is a vital practice for empowering the education system and requires no introduction to any academician. In the OBE, one of the important elements is measuring and monitoring the programme outcomes (POs). The process of collecting data has always been tedious and is required to be improved. In this paper, the mechanism of analyzing the program outcomes as one of the fundamental factors for the accreditation in FKE UiTMPP is presented. The tool was developed by the OBE committee unit and known as OBEANAS system to obtain the overall program outcomes performance of EE220 program in UiTMPP. The system was designed using oriented programming C# as graphical user interface (GUI) and the server system involves Microsoft SQL Server 2012 (MSSQL 2012). The OBE-ANAS system must comply with the Key Performance Indicators (set by the top management) as targeted indicator where students are expected to achieve a score as a minimum 50% or level 2 to attain the respective PO. At the end of the process, the tool provides better platform for observing and measuring POs parameters such as POs average, POs density, individual POs and Degree of Programme Achievement (DPA) achievement analysis. The developed system is believed to benefit the faculty in terms of accreditation and achieving the KPI.